ARTIFICIAL INTELLIGENCE INTEGRATION IN ENGLISH LANGUAGE TEACHING: PERSPECTIVES OF SPORT SCIENCE EDUCATION STUDENTS - Rachmawati, Umi; Yunianti, Sukma Shinta; Agustyaningrum, Nina (Linguists : Journal of Linguistics and Language Teaching, 2025)
Artificial intelligence education in the era of society 5.0 becomes widely used for in English language learning for many purposes. This study is aimed at finding the students’ perspectives on their needs of English language learning for a specific purpose in the field of sport science educations with the use of artificial intelligence as the teaching and learning media. The importance of needs analysis in the initial process of teaching and learning is conducted to gather information that will justify the learning goals, process including the methods, learning media, and the learning activities, and the evaluation of their learning to the betterment of the students’ learning achievement. The needs analysis was conducted through a qualitative design study with the use of questionnaires to gather the data from the subject of the study. This study is a qualitative study focusing on the needs analysis of the artificial intelligence use in English language learning for sport education study program. The subject of the study is university students of Sport Science Education, Faculty of Social Science Education and Sport Science Education in a private university in Indonesia. The data were gathered through questionnaire and observation on the subject. The questionnaire was administered following the criteria of needs analysis including the needs, necessities, wants, and lacks. The observation was conducted during the teaching and learning process of English in sport science study program. The data were analyzed qualitatively. The results of the study present that the students’ needs on the learning English is high that is aimed at enabling the students’ access any scientific articles to complete their tasks during the study program. The use of artificial intelligence during the teaching and learning is strongly suggested to support the students in developing not only the target language but also their technological skills. However, the application of the artificial intelligence during the English class is still limited due to several challenges discussed in this article.